2012
DOI: 10.1177/0961203312456893
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and renal outcomes in lupus nephritis: an update and guide to management

Abstract: Systemic lupus erythematosis (SLE) commonly affects women of child bearing-age, and advances in treatment have resulted in an increasing number of women with renal involvement becoming pregnant. Knowledge of the relationship of the condition with respect to fertility and pregnancy is important for all clinicians involved in the care of women with lupus nephritis because they have complicated pregnancies. Presentation of lupus nephritis can range from mild asymptomatic proteinuria to rapidly progressive renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 109 publications
(216 reference statements)
1
24
0
2
Order By: Relevance
“…This is particularly important in systemic disorders such as systemic lupus erythematosus and vasculitis. It is crucial for those patients with preexisting renal disease to be in remission for 6 months prior to conception to ensure a safe and successful pregnancy [ 3 ]. Treating laboratory test results without corresponding clinical manifestations is unnecessary.…”
mentioning
confidence: 99%
“…This is particularly important in systemic disorders such as systemic lupus erythematosus and vasculitis. It is crucial for those patients with preexisting renal disease to be in remission for 6 months prior to conception to ensure a safe and successful pregnancy [ 3 ]. Treating laboratory test results without corresponding clinical manifestations is unnecessary.…”
mentioning
confidence: 99%
“…ANA was found to be positive in 92 % patients of SLE in this study. Bramham et al [10] reported that even in the presence of anti-Ro and anti-La antibodies, the incidence of myocarditis is only 2-3 % and increases to 20 % with a prior affected child. In our study, 2 fetuses had CHB diagnosed late in pregnancy, and in both the cases, mothers were found to be positive anti-Ro and anti-La antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus nephritis seems to be more common in the postpartum period. 16,17 Predictors of poor obstetric outcomes in lupus nephritis include active disease at conception and in early pregnancy, >0.5 g protein/24 hours, CKD stage >3, hypertension and the presence of antiphospholipid antibodies.…”
Section: Lupus Nephritismentioning
confidence: 99%